Stelarc and the obsolescence of the body: (bio)ethical and aesthetic considerations around the work - Salinas Quintana, Pedro (Acta Bioethica, 2025)
Based on the work of the Cypriot-Australian artist, Stelarc, this article examines some of the fundamental milestones of his work that postulate a potential obsolescence of the human body. Three clear moments are distinguished in the production of the artist’s work that serve as an argument to explain the possible paths of the human body in the face of the irruption of technology and biotechnologies. Finally, the scope of the relation between art, science and technology is questioned from a bioethical and aesthetic perspective that reflects on the figure of the cyborg.